Comparison of AFLP, ESTSSR, ISSR and SSR markers for polymorphism among recombinant inbred lines of tef (Eragrostis tef) - Chanyalew, S.; Tefera, H.; Harjit-Singh; Sorrells, M.E. (2007)
Molecular genetic analysis of tef using 85 Amplified Fragment Length Polymorphism (AFLP), 50Expressed Sequence Tag-Simple sequence Repeats (EST-SSRs), 20 Simple Sequence Repeat (SSR)and 14 Inter Simple Sequence Repeat (ISSR) was conducted using a population of 124 F7 recombinant inbred lines (RIL) to generate information on the relative capacity of the molecular marker techniques in generating polymorphism. The RI population was derived by single-seed descent method from an interspecific cross between Eragrostis tef (DZ-01-2785) and Eragrostis pilosa(Acc. 30-5). A total of 205 primers were surveyed from AFLP, EST-SSR, SSR and ISSR markers to detect poly-morphism between parents, out of which 77 (37.6%) resulted in scoreable polymorphism. A total of 166 markers have been mapped. The majority (93%) of markers segregated as dominant markers.Even though AFLP markers are known in generating a large number of fragments per reaction, inthe present study, the number of resolvable fragments and polymorphic bands per gel with EST-SSR and ISSR markers were as high as AFLP. The polymorphism level for the interspecific tef population was low (10.8%). The fact that the combination of molecular markers employed in the present study are capable of sampling sequence configuration, which provides best genome coverage, implies that the results of the present study will be more valuable for further molecular genetic study in tef.